2022
DOI: 10.1037/ebs0000242
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mating context and women’s appearance enhancement strategies.

Abstract: Previous research has indicated that men tend to prioritize facial over bodily attractiveness in long-term mating contexts but shift in the opposite direction in short-term mating contexts. The current study extended this research to test whether women adjust their appearance enhancement practices in ways that reflect men’s relative priorities. In particular, we hypothesized that women pursuing short-term relationships would report engaging in appearance enhancement tactics that increase the attractiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A similar effect might be observed among women in short-term mating contexts. There is some evidence to suggest that women are aware of men’s greater prioritization of bodily attractiveness in short-term mating contexts (Perilloux et al, 2013) and adjust their mate attraction (Cloud & Perilloux, 2020) and competitor derogation (Wyckoff et al, 2019) tactics accordingly. Thus, women with unrestricted sociosexual orientations might also be especially sensitive to the presence of intrasexual competitors with attractive bodies as such rivals pose special threat in their preferred mating context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect might be observed among women in short-term mating contexts. There is some evidence to suggest that women are aware of men’s greater prioritization of bodily attractiveness in short-term mating contexts (Perilloux et al, 2013) and adjust their mate attraction (Cloud & Perilloux, 2020) and competitor derogation (Wyckoff et al, 2019) tactics accordingly. Thus, women with unrestricted sociosexual orientations might also be especially sensitive to the presence of intrasexual competitors with attractive bodies as such rivals pose special threat in their preferred mating context.…”
Section: Discussionmentioning
confidence: 99%
“…As research over the past 3 decades suggests, women whose WHRs fall at the low end of the typical female range (i.e., .68-.72) are considered particularly attractive. Dozens of studies have revealed this preference through the use of stimulus sets (e.g., Singh, 1993), but this effect has also been shown using actual photographs (Brase & Walker, 2004;Henss, 2000;Wilson et al, 2005), colored and blackened silhouettes (Ko sci nski, 2014), participant drawings (Cloud & Perilloux, 2015), online advertisements of female escorts (Saad, 2008), and archival data from 16th century British literature and ancient Indian, Egyptian, Greco-Roman, and African sculptures (Singh, 2006;cf. Swami et al, 2007).…”
mentioning
confidence: 98%